Meta-analysis with individual data of functional outcomes following Aquablation for lower urinary tract symptoms due to BPH in various prostate anatomies. Issue 1 (24th June 2021) - Elterman, Dean; Gilling, Peter; Roehrborn, Claus; Barber, Neil; Misrai, Vincent; Zorn, Kevin C; Bhojani, Naeem; Te, Alexis; Humphreys, Mitch; Kaplan, Steven; Desai, Mihir; Bach, Thorsten
Abstract : Objectives: To evaluate functional outcomes following Aquablation in various prostate volume and anatomical subgroups. Design: A meta-analysis with individual patient data undergoing Aquablation therapy from four prospective, global, clinical studies that have been conducted with Aquablation; WATER, WATER II, FRANCAIS WATER and OPEN WATER. Setting: Australia, Canada, Lebanon, Germany, New Zealand, UK and the USA. Participants: 425 men with lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) with 1-year follow-up. Interventions: Aquablation therapy is an ultrasound guided, robotically executed waterjet ablative procedure for the prostate. Main outcome measures: The analyses focus International Prostate Symptom Score (IPSS), uroflowmetry, postoperative Incontinence Severity Index (ISI) and surgical retreatment. Results: 425 men with prostates ranging in size from 20 to 150 mL underwent Aquablation therapy. The outcomes from the seven questions in the IPSS questionnaire were grouped by the following; prostates <100 mL, prostates ≥100 mL, prostate anatomy with an obstructive median lobe identifed by imaging, and prostate anatomy without an obstructive median lobe. Regardless of subgroup, all outcomes are consistent and demonstrate a significant improvement from baseline. Specifically, improvements in frequency, urgency and nocturia demonstrated bladder function improvement. Patients entering treatment with severe incontinence, ISI score >4, and regardless of prostate size, showed a reduction in incontinence during patient follow-up. Surgical retreatment due to BPH symptoms occurred in 0.7% (95% CI 0.1%–2.0%). Conclusions: Across a variety of prostate anatomies, Aquablation therapy showed remarkable functional improvements following the index procedure. Additionally, men with moderate to severe LUTS/BPH and overactive bladder resulting in urge incontinence showed a reduction in incontinence symptoms postprocedure.